Design Optimization of Composite Elliptical Deep-Submersible Pressure Hull for Minimizing the Buoyancy Factor. (23rd July 2014) - Fathallah, Elsayed; Qi, Hui; Tong, Lili; Helal, Mahmoud
Abstract : The design of deep submersible pressure hull's structural is one of the core technologies of submersible development of human history. Submersible pressure hulls with fiber-reinforced multilayer constructions have been developed in the recent years as substitutes for classical metallic ring-stiffened pressure hulls; strength and stability are its top priority. This paper investigates the optimum design of a composite elliptical deep-submerged pressure hull under hydrostatic pressure to minimize the buoyancy factor of the submersible pressure hull under constraints on the failure criteria and the buckling strength of the hulls to reach the maximum operating depth. The thickness and the fiber orientation angles in each layer, the radii of the ellipse, and stringers dimensions were taken as design variables and determined in the design process. The optimization procedures are performed using commercial finite element analysis software ANSYS. Additionally, a sensitivity analysis is performed to study the influence of the design variables on the structural optimum design. Results of this study provide a valuable reference for designers of underwater vehicles.